Nephroprotective effect of aloe vera extract with regulation of oxidative stress, apoptosis and aquaporin 3 expression levels in streptozotocin induced iabetic rats - YÜKSEL, MERAL (My University, 2023)
Objective: In this study we examined the protective activity of Aloe vera with considering antioxidant, anti-apoptotic properties, and the status of Aquaporin 3 (AQP3) channel protein. Material and Method: Twenty-one adult female rats were divided into three groups (n=7); Control, Diabetes, Treatment. Control group did not expose to any application. Animals in Diabetes and Treatment were exposed to experimental diabetes with administration of streptozotocin. Rats in Treatment received 300 mg/kg Aloe vera extract daily for 14 days. Rats were sacrificed and kidney samples were used for analyses. Result and Discussion: Analyses indicated that lowest malondialdehyde (MDA) and luminol levels in control group were increased significantly (P<0.05) in diabetic animals. Severe pathological changes observed in Diabetes group while microscopic examinations. Bax, Caspase-3 and apoptotic index (AI) were elevated significantly (P<0.05) in this group compared to Control. Oxidative stress, apoptotic protein expression levels and TUNEL Assay positive cell ratio were down-regulated in Treatment group. When AQP3 levels were measured, immunopositivity reduced significantly (P<0.05) in cortical kidney of Diabetes group which is normalized significantly in Treatment group.This study reporting anti-diabetic potency of Aloe vera extract has capability to avoid streptozotocin induced diabetic renal injury via regulating anti-apoptotic and anti-oxidant cellular signaling. Furthermore, Aloe vera consumption in diabetes might regulate AQP3 levels. Although we observed promising results, more studies are required to explore anti-diabetic, anti-hyperglycemic and nephroprotective activity of Aloe vera.

Amaç: Bu çalışmada Aloe vera'nın koruyucu aktivitesini antioksidan, anti-apoptotik özellikleri ve Aquaporin 3 (AQP3) kanal proteininin durumu dikkate alınarak inceledik. Gereç ve Yöntem: Yirmi bir yetişkin dişi sıçan Kontrol, Diyabet, Tedavi olmak üzere üç gruba (n=7) ayrıldı. Kontrol grubu herhangi bir uygulamaya maruz bırakılmadı. Diyabet ve Tedavideki hayvanlar, streptozotosin uygulanarak deneysel diyabete maruz bırakıldı. Tedavideki sıçanlara 14 gün boyunca günde 300 mg/kg Aloe vera özütü verildi. Sıçanlar sakrifiye edildi ve analizler için böbrek örnekleri kullanıldı. Sonuç ve Tartışma: Analizler control grubundaki en düşük malondialdehit (MDA) ve luminal düzeylerinin diyabetik hayvanlarda anlamlı olarak arttığını (P<0.05) gösterdi. Diyabet grubunda mikroskobik incelemelerde ciddi patolojik değişiklikler gözlendi. Bax, Kaspaz-3 ve apoptotic indeks (AI) bu grupta Kontrol'e gore anlamlı olarak yüksek bulundu (P<0.05). Tedavi grubunda oksidatifstres, apoptotik protein ekspresyon seviyeleri ve TUNEL Assay pozitif hücre oranı aşağı regüle oldui. AQP3 düzeyleri ölçüldüğünde, Tedavi grubund aanlamlı olarak normalize edilen immünopozitiflik, Diyabet grubunun kortikal böbreğinde önemli ölçüde azaldı (P<0.05). Bu, Aloe veraekstraktının anti-diyabetik gücünü bildiren, anti-apoptotik ve antioksidan hücresel sinyallemeyi düzenleyerek streptozotosin kaynaklı diyabetik böbrek hasarını önleme yeteneğine sahip olduğunu göstermektedir. Ayrıca, diyabette Aloe vera tüketimi AQP3 seviyelerini düzenleyebilir umut verici sonuçlar gözlemlememize rağmen, Aloe vera'nın anti-diyabetik, anti-hiperglisemik ve nefroprotektif aktivitesini keşfetmek için daha fazla çalışmaya ihtiyaç vardır
Aloe vera ekstraktının streptozotosin indüklü diyabetık ratlarda oksidatif stress, apoptozis ve aquaporin 3 ekspresyon düzeyini düzenleyerek nefroprotektif etkisi
Keywords: Tıp; Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Farmakoloji ve Toksikoloji; TROPİKAL TIP; FARMAKOLOJİ VE ECZACILIK; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; PHARMACOLOGY & TOXICOLOGY; TROPICAL MEDICINE; PHARMACOLOGY & PHARMACY; Farmakoloji; Farmasötik bilim; Pharmacology; Pharmaceutical Science; Aloe vera; apoptosis; aquaporin 3; diabetes; kidney; Aloe vera; apoptosis; aquaporin 3; diabetes; kidney; Aloe vera; apoptoz; aquaporin 3; böbrek; diyabet